Memanfaatkan Teknologi untuk Pendidikan: Membantu Siswa Belajar Online di SMA Parulian - RL Harmadi Tamba; Riswan Limbong; Kristian Siregar (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program titled "Leveraging Technology for Education: Supporting Online Learning for Students at SMA Parulian" aims to enhance the effectiveness of online learning by implementing modern technology at SMA Parulian. Given the challenges posed by the COVID-19 pandemic and the growing need for remote education, many students face difficulties in accessing and utilizing digital learning resources. This program includes training for both teachers and students on the use of online learning tools and platforms, including virtual classroom management, effective interaction techniques, and access to digital educational resources. Additionally, it provides technical support and supplementary learning materials to help students adapt to the online learning environment. Evaluation results indicate a significant improvement in students' digital skills and teaching effectiveness after the training. Students reported enhanced understanding of the material and increased engagement during online classes, while teachers felt more confident in managing virtual classrooms and utilizing technology in their teaching practices. The program demonstrates that effective implementation of technology can improve online learning experiences and address some of the challenges encountered in remote education. Future recommendations include ongoing training and further development of digital resources to support sustained and effective learning.